Population Assessment of Sulawesi’s Endangered Snoring Rails (Aramidopsis plateni Blasius) in Gandang Dewata National Park - Putera, Alexander Kurniawan Sariyanto; Nasir, Yusrianto; Rusmidin, Rusmidin; Nuruliawati, Nuruliawati; Berryman, Alex J. (Biosaintifika: Journal of Biology & Biology Education, 2023)
This study focuses on assessing the critically endangered mandar dengkur, or snoring rails (Aramidopsis plateni Blasius 1886), within Indonesia's Gandang Dewata National Park. Despite its importance in regional biodiversity, the species remains poorly documented. The primary objectives of this research are to investigate the population and ecological role of the mandar dengkur in Gandang Dewata National Park. It aims to understand their population status, the factors influencing their survival, and the level of global threats facing this species. Field surveys from July to August 2023 employed point counts and interviews with local residents, revealing a population of 20 snoring rails. Tondok Bakaru was identified as the primary subpopulation, with the highest count and probability of occurrence. Tondok Bakaru, characterized by remote and isolated areas, plays a crucial role in snoring rails' survival, mirrored by discoveries of other sensitive species like the Anoa. Environmental variables analysis through Generalized Linear Modeling (GLM) identified the nearest food source and settlement as significant factors influencing snoring rail populations, aligning with their elusive nature. The selected GLM model highlighted the impact of average NDVI, distance to the nearest food source, and distance to the nearest settlement on snoring rail density, guiding conservation efforts. This study underscores the urgency of upgrade the snoring rails' conservation status to Endangered (EN) and implementing global conservation measures by improving data collection with technology.